Analysing China`s drive for Olympic success in 2008 - Tan, T.-C.; Green, M. (The International Journal of the History of Sport, 2009)
The eyes of the world will be on Beijing in 2008 as China hosts the summer Olympic Games for the first time. A major criterion of success for China will be the ability of its athletes to win (large numbers of) Olympic medals. Yet, although there is a growing literature that explores the experiences of Western nations in their attempts to construct systems for supporting elite (Olympic) athlete development, we have very little in-depth information in this regard about China. Therefore, drawing on a framework of ten elements considered crucial for Olympic success in the West, this article explores China`s construction of an elite development system as it strives for Olympic glory in Beijing. Our analysis reveals that there is a remarkable degree of similarity in the mechanisms in place in China with those evident in (Western) nations as diverse as Australia, Canada, New Zealand and the United Kingdom. At the same time, however, it is also evident that subtle `domestic` (national) variations are apparent in the implementation of these mechanisms in China, thus indicating the significance of a nation`s political and cultural histories and traditions.